Cytotoxic Constituents from Vietnamese Marine Sponge Haliclona oculata (Linnaeus, 1759) - Van Kiem, Phan; Thi Viet Thanh, Nguyen; Thi Thuy Hang, Dan; Thi Cuc, Nguyen; Xuan Nhiem, Nguyen; Hai Yen, Pham; Le Tuan Anh, Hoang; Huu Tai, Bui; Thi Thao, Do; Van Minh, Chau (Letters in Organic Chemistry, 2015)
Using various chromatography methods, five steroids and two brominated lipids (1-7), 3β- hydroxy-5-cholenic acid methyl ester, stigmasta-5,24(28)-dien-3β,29-diol, 24-methylenecholest-4-en- 3β,6β-diol, cholest-5-en-3β,7β-diol, 24-vinylcholest-5-en-3β,24-diol, xestospongiene A, and xestospongiene J, respectively, were isolated from the methanol extract of Vietnamese marine sponge Haliclona oculata (Linnaeus, 1759). Their structures were elucidated by 1D-, 2D-NMR, and ESI-MS spectra and in comparison with those reported in the literature. Compounds 1-4, 6, and 7 were reported from Chalinidae family for the first time. In addition, all compounds were evaluated for eight human cancer cell lines as HepG-2, KB, LU-1, MCF-7, LNCaP, HL- 60, SK-Mel2, and PC-3. As shown in results, compound 2 showed significant cytotoxic activities on KB and LU-1 cancer cell lines with the IC50 values ranging from 8.74 to 9.32 μM.
Keywords: steroid